Histochemical characterization of oocytes in the pink Cuskeel (Genypterus blacodes) - Cohen, Stefanía (2015)
In the present study we histochemically and lectinhistochemically characterized the growing oocytes of the pink cuskeel (Genypterus blacodes). We used histochemical methods for the localization and characterization of glycoconjugates (GCs) and lectin histochemical techniques for the identification of specific sugar residues. We analyzed presence and distribution of GCs in the different structures of the growing follicles (cortical alveoli, globules, yolk granules and zona radiata). During the initial stage of vitellogenesis, the oocytes presented small yolk granules composed of GCs that gradually increased during exogenous vitellogenesis. These GCs contained moderate quantities of α-D-mannose, D-glucose, N-acetylglucosamine and N-acetyl-neuraminic acid. The cortical alveoli contained both neutral and carboxylated GCs, and lectin techniques detected N-acetylgalactosamine, galactose and L-fucose. The zona radiata showed a strong positive reaction to PAS and it reacted weakly with more specific techniques, such as KOH/PAS and PA/Bh/KOH/PAS. This structure showed GCs with oxidizable vicinal diols, O-acyl sugars and sialic acid residues with different substitution types and presented N-acetylgalactosamine and L-fucose specific residues. The oocytes follicular envelope evidenced neutral and acidic non-sulfated GCs and high concentrations of α-D-mannose, D-glucose, galactose and N-acetylgalactosamine. The intergranular cytoplasmic GCs were mainly rich in α-D-mannose, D-glucose, N-acetylgalactosamine, N-acetylglucosamine and N-acetyl-neuraminic acid. These results enhance the comprehension of the structure and functionality of the pink cuskeel ovarian follicles, and provide a useful tool for the study of this tissue in other teleost species.